AN APPROACH TOWARDS PLANT LOCATION AND PLANT LAYOUT (International Journal of Engineering Sciences & Management Research, 2015)
For any kind of production one needs men, material and machinery. Men work on material with the aid of machinery and tools. In the process of production at least one of the three, men, material or machinery has to be moved depending upon the process and the product. If men, material and machinery all remain stationery there can be no production in the industrial sense. Then what is to be moved is the problem for the layout engineer. The most common element which is moved from place to place is material except when the material is big or difficult to transport, or when there is only one piece involved, or when the finished product is to remain fixed where it is to be produced. When tools and machinery are small, it is generally easy to move the tools and machinery and when machines and materials cannot be moved, the third element of production, the men are moved. There are various methods of grouping and production machinery, the common and classical types of the arrangement are fixed position layout, process layout and product layout. These classical layout are used with fabrication operations as well as in assembly, but most plants today are laid out using a combination of these classical layouts and are never seen in their pure form.